The antiapoptotic effects of conditioned medium from bone marrow-derived mesenchymal stromal stem cells on cyclophosphamide-induced testicular damage in rat: An experimental study - Zeynab Esmailpour; Soheila Madadi; Maryam Baazm (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Cyclophosphamide (CP) has some negative effects on the reproductive system. Stem cells and their metabolites are being utilized to enhance fertility after chemotherapy. Objective: This study aimed to investigate the impact of conditioned medium (CM) derived from bone marrow mesenchymal stromal stem cells (BM-MSCs) on the toxic effects of CP on testicles. Materials and Methods: BM-MSCs were isolated, a CM was collected and 25-fold concentrated. 24 male Wistar rats (8 wk, 200-250 gr) were randomly divided into following groups: control, CP, CP+ Dulbecco's Modified Eagle Medium (DMEM), CP+CM. CP was given at a single dose of 100 mg/kg. 2 wk after the CP administration, CM was injected into the testicular efferent duct. Sperm parameters, testicular histopathology, and the level of testosterone were analyzed 2 months after treatment. The expression of B-cell lymphoma 2 (Bcl2) and Bcl2-associated X protein (Bax) genes were evaluated by real-time polymerase chain reaction. Results: CP had a negative effect on testis histology (p < 0.001) and sperm quality (p < 0.001). It changed the expression of genes associated with apoptosis (p < 0.001). Treatment with CM reduced the expression of Bax (p < 0.001), while significantly increasing the expression of Bcl2 (p = 0.01). It improved sperm count (p = 0.03), viability (p < 0.001), motility (p < 0.001), spermatogonial count (p < 0.001), and epithelial thickness of testicular tubules (p = 0.02). Conclusion: These findings suggest that CM produced from BM-MSCs may be valuable for therapeutic approaches in reproductive medicine and may lessen the side effects of CP.